2012
DOI: 10.1007/s11095-012-0727-3
|View full text |Cite
|
Sign up to set email alerts
|

Reversine, a 2,6-disubstituted Purine, as an Anti-cancer Agent in Differentiated and Undifferentiated Thyroid Cancer Cells

Abstract: Data demonstrated that reversine is effective in inhibiting the growth of thyroid cancer cells by cell cycle arrest or apoptosis, especially with the more aggressive ATC and PDTC. Apoptosis was induced by the mitochondria-independent pathway. Reversine is therefore worthy of further investigation in clinical therapeutics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
41
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 26 publications
6
41
0
Order By: Relevance
“…In the present study, reversine, a substituted purine, could induce fibroblasts transformation or dedifferentiation through protein kinases (such as JAK2, SRC, and Akt) and modulation of phosphorylation (Hua et al 2012;Shan et al 2007;. Later on, research showed that it exhibited a significant antitumor activity against human cancer cells characterized by virtually uncontrolled tumour growth and spread of abnormal cells (Jemaà et al 2012;Kuo et al 2012;Hsieh et al 2007).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…In the present study, reversine, a substituted purine, could induce fibroblasts transformation or dedifferentiation through protein kinases (such as JAK2, SRC, and Akt) and modulation of phosphorylation (Hua et al 2012;Shan et al 2007;. Later on, research showed that it exhibited a significant antitumor activity against human cancer cells characterized by virtually uncontrolled tumour growth and spread of abnormal cells (Jemaà et al 2012;Kuo et al 2012;Hsieh et al 2007).…”
Section: Discussionmentioning
confidence: 74%
“…Later, some reports showed that reversine had a role in regeneration (Anastasia et al 2006;Kim et al 2007;Saraiya et al 2010;Anastasia et al 2010;Jung and Williams 2011). Moreover, a recent report showed that reversine had anti-tumor capabilities such as for a myeloma cell line (McMillin et al 2010), and demonstrated that reversine could suppress the expression of cell cycle related proteins Aurora kinase A (Aur-A) and Aurora kinase B (Aur-B), and also could suppress enzymes involved in cell growth signaling, such as JAK2 and SRC (McMillin et al 2010;Hua et al 2012;Shan et al 2007;Jemaà et al 2012;Kuo et al 2012;Hsieh et al 2007). However, the definite molecular signaling pathway of the anti-tumor effects of reversine has not yet been understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…35,[41][42][43][44][45] These findings indicate that reversine exerts relatively broad anticancer effects. Here, we show that low-dose reversine, 0.5 μM, a concentration at which reversine selectively inhibits MPS1, fails to preferentially kill TP53 -/-HCT 116 colon carcinoma cells.…”
Section: Discussionmentioning
confidence: 93%
“…Reversine has been shown to inhibit cell proliferation [18, 22], to induce cell-cycle arrest at the G2/M phase [1, 3, 22-24], to trigger apoptosis [3, 5, 10, 23-27], to induce cell swelling with polyploidy [1, 9, 23, 27], and to stimulate autophagy [3, 10, 24]. …”
Section: Introductionmentioning
confidence: 99%